EFEKTIVITAS DAN EFISIENSI KINERJA DINAS PEKERJAAN UMUM KABUPATEN ENREKANG - Nurmiati, Nurmiati; Lubis, Bastian; Yanti, Irma (Universitas Patria Artha, 2023)
This research was conducted to assess the Effectiveness and Efficiency of performance at the Enrekang Regency Public Works Office. The method used in this study is a quantitative descriptive method, namely analyzing the realization of the 2018 to 2021 Public Works Department budget and expenditure budget using effectiveness ratios and efficiency ratios. The results of the study show that the levels and criteria for the effectiveness of using the budget and the realization of the Enrekang Regency Public Works Office for 2018-2021 vary widely. The implementation of the 2018-2021 Expenditure Budget is said to be quite effective Judging from these calculations, the performance of the Enrekang Regency Public Works Office is quite effective because the average result achieved is 84.26%, while for budget calculations regarding the level of efficiency in spending each year the criterion is said to be efficient because based on 2018 calculations it was 80.20%, year 2019 amounted to 77.86%, 2020 amounted to 78.80% and 2021 amounted to 13.09%. Judging from these calculations, the performance of the Enrekang Regency Public Works Office is efficient because the average result achieved is 62,48%.